SUFISM AS SCIENTIA SACRA ACTUALIZED IN TRADITION AND RELIGION (PERSPECTIVE OF SAYYED HOSSEIN) - Zairotus Sholikah (Journal of Islamic Studies and Humanities, 2023)
Spiritual crises often occur in today's modern society which is trapped in human modernity. This gap results in a lack of divine knowledge (perennialism) which is in human nature. This study is intended to answer the question How is the relation of Sufism as sacred knowledge embodied in religion and tradition. This research is a qualitative research with a philosophical approach. The research location as a source of data through interviews, participant observation, and documentation. All data were analyzed using the concepts of knowledge and holiness Sayyed Hossein Nasr with scientia sacra knowledge. This study shows that perennialism and Sufism have a relationship in explaining the purpose and nature of religion, namely "Divine knowledge". The relationship between the two was put forward by Seyyed Hossein Nasr, perennialism can be equated with nature so as to give rise to transcendence. Between the two there is the same goal, to function religion as a way for humans to get closer to God.